2014
DOI: 10.1586/17434440.2015.975116
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic self-expanding dilation technology for treatment of sinusitis: the Vent-Os sinus dilation system

Abstract: The Vent-Os Sinus Dilation System is an osmotically driven device that provides a means to access the sinus space and to dilate the maxillary sinus ostia and associated spaces in adults for diagnostic and therapeutic procedures. Unlike balloon dilation devices that use rapid, high-pressure inflation, this self-expanding device is designed to gently and gradually open the maxillary ostia. The procedure can be safely and easily completed in-office with minimal anesthetics and analgesics on board. Clinical result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Zur ambulanten Insertion in das Kieferhöhlenostium wurde ein spezieller, nicht resorbierbarer Stent ("Vent-Os") entwickelt, welcher durch osmotische Kräfte nach Insertion einen bewussten Dilatations-Effekt erzielt [68,69].…”
Section: Stent Zur Osmotischen Dilatation (‚Vent-os Sinus Dilation Syunclassified
“…Zur ambulanten Insertion in das Kieferhöhlenostium wurde ein spezieller, nicht resorbierbarer Stent ("Vent-Os") entwickelt, welcher durch osmotische Kräfte nach Insertion einen bewussten Dilatations-Effekt erzielt [68,69].…”
Section: Stent Zur Osmotischen Dilatation (‚Vent-os Sinus Dilation Syunclassified
“…For example, a simple mechanical device can be deployed to dilate the maxillary or frontal sinus ostia in much the same manner as BSP, but utilizing osmotic forces to expand gradually over a period of 1 hour. This has been demonstrated to be well tolerated, suitable for use in the outpatient clinic, and with shortterm outcomes comparable with BSP, 25,26 but has seen limited adoption so far compared with BSP procedures.…”
Section: Novel Office-based Proceduresmentioning
confidence: 99%
“…Feasibility studies have demonstrated that it is a safe, effective technology that is acceptable to both patients and surgeons. 25 Certainly, the device has appeal for patients either unfit or unwilling for polypectomy under a general anesthetic. Further evaluation of the technology with direct comparison of outcomes and cost-effectiveness of office polypectomy with the gold standard of endoscopic surgery with adjuvant polypectomy is required before conclusions about its generalizable appeal can be made.…”
Section: Novel Office-based Proceduresmentioning
confidence: 99%